High-performance activated carbon fiber derived from pineapple leaf fiber via Co(II)-assisted preparation revealed surprising capacitive-pseudocapacitive synergistic charge storage - Meekati T. (2023)
Activated carbons (ACs) are mostly inexpensive and widely used as active materials for supercapacitors. Here, we report the preparation of porous activated carbon fiber derived from pineapple leaf fiber (PAC) via sequential carbonization and Co2+/KOH and CO2 activation. A combination of oxygen-containing groups on the optimal micro-mesoporous carbon surface and high specific surface area of the synthesized activated carbon fiber resulted in high specific capacitance of 400 F g−1 at 0.1 A g−1 as well as a surprising rate capability of 186 F g−1 even at 60 A g−1. The PAC structure also significantly affects superb cyclability (~86 % capacitance retention, over 10,000 cycles at 20 A g−1). The assembled PAC symmetrical cell also delivered an energy density of 11.94 Wh kg−1 at a power density of 92.35 W kg−1 in ionic liquid with ultra-long life of 94.50 % over 10,000 continued charge/discharge cycles (at 1 A g−1). This work provides more information on a porous activated carbon fiber from PALF, which will be utilized, and a developed strategy route for biomass after the post-harvest.